Enhancing Inter-Data Centre Link Security with Spectral Polarisation Shuffling and Phase Encoding - Nogueira, Marcelo Pereira [UNESP]; Badue, Nairton José; Bonani, Luiz Henrique; Aldaya, Ivan [UNESP]; Abbade, Marcelo Luis Francisco [UNESP] (Institute of Electrical and Electronics Engineers (IEEE), 2023)
In this work, we propose a strategy for encrypting dual polarisation optical signals. The scheme is based on shuffling the spectral samples of baseband signals that further modulate the orthogonal polarisations of an optical carrier. Additionally, the samples phases are also encoded. We investigate the performance of the encryption scheme in a scenario where data centres are connected by a cascade of standard fibre optical links. Simulation results indicate that the encrypted versions of 448 Gb/s 16 - quadrature amplitude modulation (QAM) signals may be properly propagated by distances of up to 420 km.
Keywords: Network security; optical communications; signal cryptography